Positive and Negative Impacts of Renewable Energy Sources - Vezmar, Stanislav; Spajić, Anton; Topić, Danijel; Šljivac, Damir; Jozsa, Lajos (International Journal of Electrical and Computer Engineering Systems, 2014)
In this paper, positive and negative impacts of renewable energy sources are presented. Impacts of solar power, biomass power, fuel cells, hydro power, wind power and geothermal power are described. Ecological, social and political impacts of different renewable energy sources are described. Impacts of power plants using different renewable energy sources on the power grid are also described.